2022
DOI: 10.1002/jcla.24591
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0129047 regulates the miR‐375/ACVRL1 axis to attenuate the progression of lung adenocarcinoma

Abstract: Background Circular RNAs (circRNAs) are attractive candidates to be used as biomarkers of human cancers, including lung adenocarcinoma (LUAD). Our study aimed to investigate the functions and regulatory mechanisms of hsa_circ_0129047 in the tumorigenesis of LUAD. Methods Reverse transcription‐quantitative polymerase chain reaction was performed to determine the circRNA, microRNA (miRNA), and mRNA expression levels in LUAD cell lines and tissues. Tumor xenografts were es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…ACVRL1 has been shown to primarily participate in the formation of blood vessels, and mutations of this gene can cause various hemorrhagic disorders[ 21 - 23 ]. Furthermore, the heightened expression of ACVRL1 through transcriptional activity exhibits anti-tumor properties in lung adenocarcinoma cells[ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…ACVRL1 has been shown to primarily participate in the formation of blood vessels, and mutations of this gene can cause various hemorrhagic disorders[ 21 - 23 ]. Furthermore, the heightened expression of ACVRL1 through transcriptional activity exhibits anti-tumor properties in lung adenocarcinoma cells[ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that circ_0129047 is downregulated in HCC tissues and cells ( Figure 1 ). According to previous studies, circ_0129047 was reported to play an antitumorigenic role in lung adenocarcinoma [ 11 , 24 ]. However, the role of circ_0129047 in HCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, cytoplasmic circRNAs compete for miRNA binding and modulate mRNA turnover [ 25 ]. circ_0129047 suppresses the progression of lung adenocarcinoma by binding to miR-375 [ 24 ] or miR-1206 [ 11 ]. In contrast to previous studies on lung adenocarcinoma, we found that circ_0129047 recognizes miR-492 and downregulates its expression in HCC cells ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely acknowledged that miRNAs are involved in circRNA's biological effects [28][29][30]. Intriguingly, CSCD database [21] analysis revealed that hsa_circ_0037858 possessed potential microRNA response elements.…”
Section: Discussionmentioning
confidence: 99%